Response of carbonate factories to late Paleozoic climate change: a case study from the Yanduhe section, Hubei Province, South China - Huang, Zihang; Yi, Xuefei; Huang, Yunfei; Tian, Li; Wu, Kui; Li, Mengfan (Frontiers in Marine Science, 2025)
The carbonate factory concept was proposed to understand the spatial dynamics and processes involved in carbonate production, which was heavily influenced by climate change. The Permian period witnessed several significant climate change events that had a considerable impact on the carbonate factory. However, research on how the carbonate factory responded to these climate change events during the Permian is still limited. In this study, a detailed analysis of carbonate microfacies was conducted in the Yanduhe section, western Hubei Province, South China, to investigate the relationship between the carbonate factory and climate change. Ten sedimentary microfacies were detected, and classified into three microfacies associations, which correspond to different environments of inner ramp, middle ramp, and outer ramp. Meanwhile, eight transgression-regression sequences were identified, revealing a sea-level change trend consistent with observations from other regions in South China. Furthermore, six types of carbonate factories were recognized and five changes in carbonate factories were observed. Among those five changes, two occurred during the Late Kungurian and Late Wuchiapingian respectively, and may be attributed to climate changes, while one at the end-Guadalupian likely resulted from both the end-Guadalupian mass extinction and climate change. The other two changes in carbonate factories were caused by sea-level fluctuations. In addition, climate change affects sea surface temperature and sea levels, thereby regulating the biological communities involved in carbonate production and driving a shift in the types of carbonate factories.